2020
DOI: 10.1021/acs.jpclett.0c00193
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence in Molecular Electron Spin Qubits: Insights from Quantum Many-Body Simulations

Abstract: Quantum states are described by wave functions whose phases cannot be directly measured, but which play a vital role in quantum effects such as interference and entanglement. The loss of the relative phase information, termed decoherence, arises from the interactions between a quantum system and its environment. Decoherence is perhaps the biggest obstacle on the path to reliable quantum computing. Here we show that decoherence occurs even in an isolated molecule although not all phase information is lost via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…3). An example of this interaction occurs in Co(II) complexes, from the coupling of the magnetic nucleus of 59 Co (I ¼ 7 2…”
Section: Basic Molecular Spin Properties Relevant To Relaxationmentioning
confidence: 99%
See 2 more Smart Citations
“…3). An example of this interaction occurs in Co(II) complexes, from the coupling of the magnetic nucleus of 59 Co (I ¼ 7 2…”
Section: Basic Molecular Spin Properties Relevant To Relaxationmentioning
confidence: 99%
“…Many metal ions possess isotopes that have non-zero nuclear spin, e.g. 59 Co (I ¼ 7 2 , 100% natural abundance) or 165 Ho (I ¼ 7 2 , also 100% natural abundance). The impact of a non-zero nuclear spin is primarily observed at zero field, low temperatures, and primarily affects quantum tunneling mechanisms.…”
Section: Isotopic Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that there is a barrier which we will describe by some distance r o where for 13 C nuclear spins located at distances r > r o , spin decoherence of the XV − center is produced because of entanglement, while for 13 C nuclear spins located at distances r < r o spin coherence of the XV − center is actually enhanced. [36] These two regions are separated by a barrier to spin diffusion as originally suggested by Bloembergen. [37] One interesting application of this spin diffusion barrier might be considered when we try to create a network of XV − centers in diamond experimentally.…”
Section: Resultsmentioning
confidence: 88%
“…[15][16][17][18] Several fields in quantum measurement, from ion traps to atomic clocks and molecular magnets, take advantage of avoided crossings between various spin sublevels to dampen noise caused by fluctuating magnetic fields. 15,[18][19][20][21][22] At the avoided crossings with respect to the applied Zeeman field, transition frequencies become insensitive to field fluctuations because their first derivative with respect to the magnetic field vanishes. Transitions at these points are called "clock transitions," (CTs) because of their history in atomic clocks.…”
Section: Introductionmentioning
confidence: 99%